2022
DOI: 10.1038/s41598-022-14147-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of the presence of allergic disease with subsequent risk of liver cancer in a nationwide retrospective cohort among Koreans

Abstract: A number of studies have proposed an inverse association between allergic diseases and risk of cancer, but only a few studies have specifically investigated the risk of primary liver cancer, including hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). The aim of this study was to evaluate the association of allergic diseases with risk of primary liver cancer. We conducted a retrospective cohort study of the Korean National Health Insurance Service database consisted of 405,512 Korean adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Similar positive associations were observed for type 1 diabetes and systemic lupus erythematosus [44,45]. Kim et al reported a significantly negative association (multivariable-adjusted hazard ratio = 0.80) between asthma and liver cancer [46]. However, using MR analyses, we did not detect a genetic association between these inflammatory diseases and liver cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Similar positive associations were observed for type 1 diabetes and systemic lupus erythematosus [44,45]. Kim et al reported a significantly negative association (multivariable-adjusted hazard ratio = 0.80) between asthma and liver cancer [46]. However, using MR analyses, we did not detect a genetic association between these inflammatory diseases and liver cancer.…”
Section: Discussionsupporting
confidence: 82%
“…The strengths of the present study included a large cohort of patients from multiple hospitals and the adjustment of confounders, including age, sex, comorbidities, laboratory data of liver function tests, and comedications. To mitigate potential confounding by indication, diseases with antihistamine indications were incorporated as covariates [ 39 , 40 ]. Furthermore, sensitivity and validation tests were conducted, which yielded consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cohort studies conducted in England and Denmark revealed no indication of an association between AD and most cancers, with the exception of lymphoma 8 . However, some studies showed clearly reduced risks for some other types of cancer 9,10 . For instance, a population‐based study in Korea involving a total of 24,089 participants found that AD was significantly associated with a reduced risk of gastric cancer 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 However, some studies showed clearly reduced risks for some other types of cancer. 9,10 For instance, a population-based study in Korea involving a total of 24,089 participants found that AD was significantly associated with a reduced risk of gastric cancer. 10 So far, the evidence connecting AD and cancer risk in humans has been based on observational studies, which are susceptible to confounding and reverse causation.…”
Section: Introductionmentioning
confidence: 99%